Determination of Traces of Pd(II) in Spiked Samples by Using 3,4-Dihydroxybenzaldehydeisonicotinol-hydrazone as a Chelating Agent with UV Visible Spectrophotometer - S. Lakshmi Narayana; C. Ramachandraiah; A. Varada Reddy; Dongyeun Lee; Jaesool Shim (E-Journal of Chemistry)
A simple, rapid, sensitive and inexpensive method has been developed for the determination of trace amounts of palladium(II) using 3,4-dihydroxybenzaldehydeisonicotinoylhydrazone (3,4-DHBINH). The metal ion gives a yellow colored complex with 3,4-DHBINH in acetate buffer of pH 3.0 with 1:1 (metal: ligand) composition. The complex shows maximum absorption at 380 nm. Beer’s law is obeyed in the range 0.5-20.0 ppm of Pd(II). The molar absorptivity, Sandell’s sensitivity and detection limit were found to be 0.53×104 L mol-1 cm-1, 0.02 μg cm-2 and 0.0948 μg mL-1, respectively. The correlation coefficient and regression coefficient of the Pd(II)-3,4-DHBINH complex were 1.08 and 0.04 respectively. Major cations and anions did not show any interference. Anti-microbial activity of the Pd(II)-3,4-DHBINH has been studied. The developed method has been successfully applied to the analysis of Pd(II) in spiked samples. Comparing the results with those obtained using an atomic absorption spectrophotometer tested the validity of the method